Utilization of Nyamplung Oil as an Active Ingredient in an Antioxidant Facial Clay Mask - Amelia, Okta; Yunira, Eka Nur’azmi; Larassati, Dyah Putri; Trimolaksono, Untung (Agroindustrial Journal, 2025)
Nyamplung oil has active components that are beneficial to skin health due to its high antioxidant content. Nyamplung oil serves as an active element in clay masks. This study uses nyamplung oil, which is high in antioxidants, to harness the renewing and skin regenerating qualities of this natural component. The study involved creating a clay mask with various concentrations of nyamplung oil (4%, 6%, 8%) and xanthan gum (0.6% and 0.8%), and then analyzing its antioxidant activity. The clay mask formulated with 6% nyamplung oil and 0.8% xanthan gum demonstrated strong antioxidant activity (IC50 = 88.29), with a drying time of 5.6 minutes, a pH of 5.56, and a viscosity of 92.2 cP. Conclusion: The results demonstrate that nyamplung oil is a potent natural antioxidant suitable for cosmetic applications. The clay mask formulation with 6% nyamplung oil and 0.8% xanthan gum showed excellent physicochemical properties and very strong antioxidant activity, indicating its potential as an effective facial skin care product.